MEMS and Nanotechnology, Volume 5 Proceedings of the 2015 Annual Conference on Experimental and Applied Mechanics - Prorok, Barton C.; Starman, LaVern; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
The 16thInternational Symposium on MEMS and Nanotechnology, Volume 5 of the Proceedings of the 2015SEM Annual Conference& Exposition on Experimental and Applied Mechanics, the fifth volume of nine from the Conference, brings together contributions to this important area of research and engineering.  The collection presents early findings and case studies on a wide range of areas, including: Microscale and Microstructural Effects on Mechanical Behavior Dynamic Micro/Nanomechanics In-situ Techniques Mechanics of Graphene Indentation and Small Scale Testing MEMS.
From the Contents: Oxide Driven Strength Degradation of (1 1 1) Silicon Surfaces -- Keynote: In situ TEM Nanomechanical Testing -- Poisson's Ratio as a Damage Index Sensed By Dual-embedded Fiber Bragg Grating Sensor -- In Situ High-Rate Mechanical Testing in the Dynamic Transmission Electron Microscope.
Keywords: Microtechnology; Microelectromechanical systems; Mechanics, Applied; Solids; Microsystems and MEMS; Solid Mechanics